Signatures of Gait Movement Variability in CKD Patients Scheduled for Hemodialysis Indicate Pathological Performance Before and After Hemodialysis: A Prospective, Observational Study - Zemp, Damiano D.; Giannini, Olivier; Quadri, Pierluigi; Rabuffetti, Marco; Tettamanti, Mauro; de Bruin, Eling D. (Frontiers in Medicine, 2021)
Background The frailty status of hemodialysis patients is well known, but the role of the therapy in the frailty process is not yet clear. Nowadays gait analysis in nephrology is neglected, although gait performance is known to be related to kidney function. We hypothesized that gait quality and physical activity level had already reduced beforehand and do not decline because of the start of hemodialysis. Methods Fourteen patients (72.3±5.7 years old) in a pre-dialysis program underwent an instrumental gait analysis and their physical activity was monitored for a week. This protocol was repeated 3, 6, 12 and 24 months after the first hemodialysis session. Results At baseline, our sample showed a conservative gait with pathologic gait variability, high dual-task cost and a sedentary lifestyle. No statistically significant change was found in any parameter in the analyzed period, but there was a tendency towards an improvement of gait quality and physical activity in the first year of treatment, and a decline in the second year. Conclusion Elderly patients in the pre-dialysis stage show a conservative gait, however variability was in a pathological range and did not change post-hemodialysis. This hints towards changes in the central nervous system due to the kidney disease. This finding suggests the importance of gait analysis in the early stages of renal disease in the diagnosis of changes in the nervous system due to kidney failure that affect gait. Early detection of these changes would potentially allow a prevention program tailored to this population to be developed.